Climate policy co-benefits: a review. (15th March 2020) - Karlsson, Mikael; Alfredsson, Eva; Westling, Nils
ABSTRACT: Concern over mitigation costs impedes the adoption of the climate policies needed to achieve agreed global warming targets. While costs are important to consider, so are benefits. However, the evidence for climate policy co-benefits, that is, the benefits in addition to avoided climate change costs, is commonly overlooked in policy-making. In many areas, the research is limited and not comprehensively synthesised. This article counters that problem and reviews 239 peer-reviewed articles, selected from 1, 749 hits from a literature search covering 'co-benefits' and related terms. Aiming to aid policy-makers and to identify research gaps, we structure, describe, analyse and synthesize the rapidly expanding knowledge on climate policy co-benefits. Improved air quality is the co-benefit category dominating the literature, but studies covering a broad geographic range also focus on diet, physical activity, soil and water quality, biodiversity, economic performance, and energy security. In these areas, co-benefits are shown to be of substantial economic value, regarding air quality often of the same order of magnitude as mitigation costs, in some instances even larger. However, the share of studies quantifying or monetizing co-benefits is limited, and the empirical evidence is small, in particular for areas besides air quality and health. Furthermore, the knowledge is seldom used in policy-making, meaning that decision-making is often biased and overly concerned with costs, leading to suboptimal climate policies and goal failures. Evidently, more research is needed, as well as improved decision-making. Understanding and acting on climate policy co-benefits can promote policies that better mitigate climate change and improve overall welfare. Key policy insights Climate policy co-benefits in well-researched fields such as air quality and health are large, often equalling or exceeding mitigation costs. Despite their significance, co-benefits are seldom considered in decision-making, leading to biased policies and goal failures. In several areas, such as diet and energy security, co-benefits are sparsely researched, but emerging evidence points to high values. More research is needed, including on how to describe the total value of different co-benefits. Improved processes, documentation requirements and criteria in decision-making are needed, in order to ensure that political decision-makers consider co-benefits.